Proposed Design of Practical Approach in Implementation of Operations Focus, Case Study in PT. X (Journal of Business and Management, 2021)
In 2020, Indonesia had experience in increasing the number of internet users up to 73,7% of the total population, which had been increased 25.5 million users from the previous years. This phenomenon, coupled with the current pandemic situation, has become one of the key factors from the rapid growth of the e-commerce industry. PT. X is one of the e-commerce based in Indonesia which provides a platform to connect farmers and producers by distributing food products to customers. Currently, PT. X has not yet implemented the Malcolm Baldrige National Quality Award in managing its product quality. Therefore, it needs to be explored the capabilities to manage quality on production processes. This research is presented a qualitative method in which in processing data collection, this research using an interview process with the COO of PT. X. The questions asked are based on the 2021-2022 Baldrige Excellence Builder, which focuses only on criteria number 6, operations focus. The answer was assessed using the Baldrige Scoring Guideline. Based on the results of interviews, data interpretation, and data assessment using the MBNQA framework, it is founded that PT. X's current operation performance is still low. The score gain is 46,75 points out of 85 points. As consequence, several improvements are needed so the company can improve its performance and increase the score to become World Class Company based on the Malcolm Baldrige National Quality Award, including designing and implementing an effective and systematic approach that is fully responsive to its multiple company requirements for the work process and operational effectiveness, the method used in future should address the work process and operational effectiveness with the company's operating environment that is well integrated with the current and future organizational needs, and improve the evaluation and improvement systems and the organizational learning through fact-based innovation.Keywords: performance management, Malcolm Baldrige National Quality Award, e-commerce